(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Efficacy of BAU-Biofungicide (3%), garlic extract (1:1), Bavistin (0.2%) and Tilt 250EC (0.2%) were evaluated against seed borne fungal pathogens of chilli collected from Lakshmonkhola, Mugarchar and Tulatuli villages under Comilla district. Four hundred seeds of each sample were tested following blotter incubation and sand culture method. Using blotter incubation method, five different seed borne fungi, namely, Colletotrichum capsici, Alternaria tenuis, Aspergillus spp, Fusarium spp, and Curvularia lunata were detected from the chilli seeds. BAU-Biofungicide (3%) and followed by garlic extracts (1:1) was found most effective among five different treatments for increasing the germination percentage as well as controlling the associated seed borne fungi in chilli seed. Highest germination percentage (89.50%) was observed in BAU-Biofungicide (3%) treated seeds. Highest reduction of Colletotrichum capsici, Alternaria tenuis, Aspergillus spp, Fusarium spp, and Curvularia lunata was observed when seeds were treated with BAU-Biofungicide (3%) and garlic extract (1:1). The highest vigour index of chilli seed collected from Lakshmomkhola, Mugarchar and Tulatuli villages were 494.56, 403.23 and 333.37, respectively was observed in BAU-Biofungicide treated seeds. J. Bangladesh Agril. Univ. 15(1): 41-46, January 2017